1996
DOI: 10.1002/(sici)1097-0215(19960717)67:2<269::aid-ijc19>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Reflux of duodenal or gastro-duodenal contents induces esophageal carcinoma in rats

Abstract: Chronic reflux esophagitis precedes Barrett's esophagus, which is defined as the columnar-lined epithelium replacing the original squamous epithelial cell lining of the esophagus. Barrett's esophagus carries a risk of malignant transformation to adenocarcinoma. Patients with complicated Barrett's esophagus reflux significantly greater amounts of both acid and duodenal contents than patients with uncomplicated Barrett's esophagus (Vaezi and Richter, 1995). Individuals with a history of gastrectomy often suffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
143
1
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 173 publications
(152 citation statements)
references
References 13 publications
6
143
1
2
Order By: Relevance
“…5,6 Repeated mucosal damage because of DGR finally induces SCC, which follows a process of initial BCH and subsequent DYS. In this study, duodenal regurgitation into the forestomach was not involved in the genesis of the columnar-lined epithelium (CLE) or ADC, in contrast to the pathogenesis in several duodenoesophageal reflux models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6 Repeated mucosal damage because of DGR finally induces SCC, which follows a process of initial BCH and subsequent DYS. In this study, duodenal regurgitation into the forestomach was not involved in the genesis of the columnar-lined epithelium (CLE) or ADC, in contrast to the pathogenesis in several duodenoesophageal reflux models.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, duodenal regurgitation into the forestomach was not involved in the genesis of the columnar-lined epithelium (CLE) or ADC, in contrast to the pathogenesis in several duodenoesophageal reflux models. 6,30,31 Miwa et al suggested that the incidence of CLE might be dependent on the amounts of duodenal contents into the esophagus. By using gastroduodenoesophageal reflux models, ADC within CLE always occurred in the lower esophagus near the anastomotic line, where more is regurgitated, and SCC surrounded by chronic squamous esophagitis was observed distant from the site of anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the esophageal perforation, the diagnosis by contrast examination reveals the occurrence of contrast runoffs in 90% of the cases investigated 9,10 . The contrast radiology of the upper gastrointestinal series did not show contrast runoff occurrences, in any of the specimens investigated, or any type of lesion that was visible even after the conduction of subsequent necropsy 14 .…”
Section: Discussionmentioning
confidence: 97%